2019
DOI: 10.1063/1.5123018
|View full text |Cite
|
Sign up to set email alerts
|

Tunable damping-like and field-like spin-orbit-torque in Pt/Co/HfO2 films via interfacial charge transfer

Abstract: The spin–orbit-torque (SOT) consists of dampinglike torque (DLT) and fieldlike torque (FLT), where the combined effects of these two torques need further consideration for efficient SOT switching. Here, the tunable correlation between the DLT and FLT is investigated in Pt/Co/HfO2 multilayers with different annealing temperatures (Ta). With increasing Ta, the FLT decreases monotonously, while both the sign and the magnitude of DLT are changed. Interfacial analysis results reveal that the tunable correlation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…[20][21][22] Moreover, a number of researches have demonstrated that both the strength and sign of λ FL /λ DL can be adjusted by tuning the material types or fabrication processes. [20,23,24] The strength of field-like torque is related to multiple factors such as layer thickness, material system, interfacial intermixing, etc. This is a complicated issue and still under exploration.…”
Section: Resultsmentioning
confidence: 99%
“…[20][21][22] Moreover, a number of researches have demonstrated that both the strength and sign of λ FL /λ DL can be adjusted by tuning the material types or fabrication processes. [20,23,24] The strength of field-like torque is related to multiple factors such as layer thickness, material system, interfacial intermixing, etc. This is a complicated issue and still under exploration.…”
Section: Resultsmentioning
confidence: 99%
“…The HfO 2 , a promising high-K and ferroelectric material, [22] has been shown to change the interfacial electron structure and enhance interface SOT when used as a capping layer. [23] Exploring the influence of HfO 2 as a buffer layer on SOT is a critical area of research, however, it remains lacking.…”
Section: Introductionmentioning
confidence: 99%
“…However, in previous studies, the heavy metals that have a role in the spin-orbit couplings are mostly composed of layered films, and the process of creating the micro-/nanostructures is expensive and time-consuming [25,26]. In this paper, construction of a type of Au@Pt NHs is provided by combining platinum with a high spin-orbit coupling effect into gold nanoparticles (AuNPs) with a surface plasmon effect.…”
Section: Introductionmentioning
confidence: 99%